2020
DOI: 10.1055/a-1293-8430
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and Left Ventricular Diastolic Function in Endurance Athletes

Abstract: The present study investigated the relationship between arterial stiffness and left ventricular diastolic function in endurance-trained athletes. Sixteen young male endurance-trained athletes and nine sedentary of similar age men participated in this study. Resting measures in carotid-femoral pulse wave velocity were obtained to assess arterial stiffness. Left ventricular diastolic function was assessed using 2-dimensional echocardiography. The athletes tended to have lower arterial stiffness than the controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…However, endurance-trained athletes have higher LV diastolic function than untrained individuals, and during incremental workloads, the stroke volume of athletes increases progressively to the maximum with no plateau 50 . In addition, we have previously reported a negative correlation between aortic stiffness and LV function 8 . Maintaining low arterial stiffness may thus reduce the workload on the left ventricle during high-intensity exercise (i. e., increase in stroke volume), which may be beneficial for V̇O 2 max.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, endurance-trained athletes have higher LV diastolic function than untrained individuals, and during incremental workloads, the stroke volume of athletes increases progressively to the maximum with no plateau 50 . In addition, we have previously reported a negative correlation between aortic stiffness and LV function 8 . Maintaining low arterial stiffness may thus reduce the workload on the left ventricle during high-intensity exercise (i. e., increase in stroke volume), which may be beneficial for V̇O 2 max.…”
Section: Discussionmentioning
confidence: 91%
“…The systolic and diastolic functions of the left ventricle influence stroke volume. LV diastolic function and maximal volume are associated with V ̇O2 max [35,36], and we have previously reported that cfPWV in endurance athletes correlated with LV diastolic function [8]. Suppression of afterload may also reduce the increase in workload of the LV myocardium (reducing the energy cost of contraction), which may improve the capacity for longer or more intense myocardial contractions during exercise [37].…”
Section: Central Arterial Stiffness and V ̇O2 Maxmentioning
confidence: 93%
See 2 more Smart Citations
“…Our study also found that patients with BMI ≥ 27.5 cm 2 had a higher prevalence of CH than normal weight patients. Several other studies [13,31,32] found that arterial stiffness influences cardiac structure and function. Our study confirmed that baPWV was correlated with LVRM and E/A, even independent of hypertension.…”
Section: Discussionmentioning
confidence: 96%